A comparison of commonly used socioeconomic indicators: Their relationship to educational disadvantage and relevance to teach first - Claire Crawford; Ellen Greaves (Institute for Fiscal Studies (IFS), 2013)
Teach First is a charity that seeks to address educational disadvantage by placing high-quality graduates as teachers in schools with the most educationally disadvantaged pupils. There are two questions to answer when deciding the appropriate way to do this. First, how does one define educational disadvantage? Second, in the absence of observing all characteristics of a pupil that define them as educationally disadvantaged, which socio-economic indicator (or combination of indicators) best predicts whether a pupil is educationally disadvantaged? This report provides an overview of free and commonly used socio-economic indicators which are available from administrative data in England. It focuses on one individual measure of socio-economic status- the pupils' eligibility for free school meals (FSM)- and three neighbourhood measures: Income Deprivation Affecting Children Index (IDACI) scores (used by Teach First to define its current eligibility criterion), Index of Multiple Deprivation (IMD) scores and local area measures of higher education (HE) participatoin known as POLAR2...
Keywords: 330